World Economic and Financial Surveys : Staff Studies, 1990. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1990)
This paper discusses commodity prices might serve as a useful leading indicator of inflation, based on the relative importance of flexible auction markets for the determination of these prices. They thus may have a tendency to respond relatively quickly, especially in response to monetary disturbances. Estimation of alternative commodity-price indexes, in which the weights are chosen so as to minimize the residual variance in aggregate inflation regressions, was not fully successful. The commodity prices do have a useful role to play as an aid in predicting inflation, so long as one is careful to interpret the relationships qualitatively and in the context of more general macroeconomic developments. The ratio of consumer to commodity price movements' changes over time, and the relative price of commodities undergoes long sustained swings; nonetheless, the qualitative linkages are quite evident in the data. Perhaps most importantly, turning points in commodity-price inflation frequently precede turning points in consumer-price inflation for the large industrial countries as a group.